The impact of allocation methods on carbon emission trading under electricity marketization reform in China: A system dynamics analysis. (15th November 2022) - Chi, Yuan-ying; Zhao, Hao; Hu, Yu; Yuan, Yong-ke; Pang, Yue-xia
Abstract: Carbon emission trading (CET) is a major institutional innovation to limit carbon dioxide emissions, which has a significant effect and influence. There are two unpaid quota allocation methods in CET, benchmark-based Vs. grandfathering. It appears meaningful to examine which allocation method can make more profit and less emission with the implementation of electricity marketization reform. Defining the allocation of the initial quota is also one of the basic points of CET. Accordingly, this paper developed a system dynamics model with different scenarios to simulate and evaluate the allocation methods with different unpaid quotas in the context of electricity reform(EMR). The results show that the grandfathering method allocation can vitalize the CET market and reduce more carbon emissions per unit, which is better than the benchmark-based method in terms of revenue, profit, investment space, and power generation. Setting a 10% unpaid quota is a benefit for steady transition. In the long term, the market on-grid price gradually shows an advantage in efficiency and liquidity. Highlights: Researched the impact of allocation methods on carbon emission trading. Constructed a different scenarios analysis by the SD method. The grandfathering allocation method is better than the benchmark-based. Setting 10% unpaid quota is benefit for steady transition. The market on-grid price takes advantage in efficiency and liquidity.